Impact of Economic Growth, Non-Renewable Consumption and Urbanization on Carbon Dioxide Emissions in OPEC Member Countries - Aram Amirnia (Pizhūhishnāmah-i Iqtiṣād-i Inirzhī-i Īrān, 2023)
The current study deals with the effect of GDP, urban population and non-renewable energy consumption on carbon dioxide emissions in OPEC member countries. To show the details of his findings, in this study, using the panel data method, the effect of GDP, increase in urban population and non-renewable energy consumption on carbon dioxide emissions for 13 OPEC member countries in the period of time, 1990 to 2019, was reviewed. The results show that GDP, urban population increase, and consumption of non-renewable fuels have a positive and significant effect on carbon dioxide emissions. The general findings indicate that following the increase in gross domestic production and the industrialization of countries, we will also witness the growth of the urban population. Environmental pollution is mainly aggravated by rapid urbanization and industrialization, as well as economic growth and non-renewable energies in OPEC member countries, which are mainly developing countries, and have destructive effects on the environment. This study recommends that sustainable urbanization and economic growth should be promoted using green finance and clean energy sources. Also, the need to change energy consumption patterns from fossil fuels and move towards renewable energy sources should be supported among OPEC member countries